2015
DOI: 10.1108/jmd-04-2015-0062
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social performance and portfolio management

Abstract: Purpose – The purpose of this paper is to assess the existence of a relationship between socially responsible behavior of companies and price trends of their stocks. Design/methodology/approach – The analysis is conducted by empirically testing data of environmental, social and governance ratings of a sample of European firms between December 2005 and December 2010. A disaggregate analysis is also performed to infer whether a specific co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, for Bajic and Yurtoglu (2018), the analysis of individual scores revealed that only the social aspect of CSP was able to influence CFP with no significant impact for the environment and governance aspects. Teti et al (2015) conducted a similar analysis for CSP measured by ESG ratings and CFP in terms of stock returns where the findings suggested that at an aggregate level, firms with higher sustainability scores had higher performance over the study period, whereas at the disaggregated level, firms with higher Escores also contributed to higher firm value. The reverse causal analysis strengthened with the GC test for CSP-CFP relationship also couldn't establish that Indian firms with higher CFP lead to more CSP at an aggregate or individual level.…”
Section: Discussionmentioning
confidence: 97%
“…However, for Bajic and Yurtoglu (2018), the analysis of individual scores revealed that only the social aspect of CSP was able to influence CFP with no significant impact for the environment and governance aspects. Teti et al (2015) conducted a similar analysis for CSP measured by ESG ratings and CFP in terms of stock returns where the findings suggested that at an aggregate level, firms with higher sustainability scores had higher performance over the study period, whereas at the disaggregated level, firms with higher Escores also contributed to higher firm value. The reverse causal analysis strengthened with the GC test for CSP-CFP relationship also couldn't establish that Indian firms with higher CFP lead to more CSP at an aggregate or individual level.…”
Section: Discussionmentioning
confidence: 97%
“…Customer loyalty can be enhanced through appropriate investment in corporate social responsibility (see Wartick, 2002, pp. 371-392;Teti et al 2015Teti et al , pp. 1144Teti et al -1160.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a strong relationship between financial returns and sustainability, explained by the level of performance for all the metrics analyzed (Carhart's alpha, Sharpe, net return, reduced cost). Ghosh, Sarmah, and Kanauzia (2020) [24]; Li et al (2020) [82] Duran-Santomil et al (2019) [92]; Kim and Lee (2018) [86]; Ganda and Milondzo (2018) [23]; Teti et al (2015) [70]; Yadav, Han, and Rho (2015) [69] With responsible management and strategy, the firms can use tools to optimize their performance, improving sustainability while not necessarily sacrificing financial outcomes and making the company more profitable and more likely to survive in the long run.…”
Section: Financial Performancementioning
confidence: 99%
“…Ajour El Zein, Consolacion-Segura, and Huertas-Garcia (2020) [94]; Han et al (2020) [1]; Awan et al (2020) [90]; Yadav, Han and Rho (2015) [69]; Teti et al (2015) [70] Efficiency gains Sustainability has been an important issue for several decades because companies want to secure competitive advantages for their future such as cost savings, consumer demand, risk mitigation, tax incentives, and using resources efficiently in saturated or competitive markets. Han et al (2020) [1]; Karlsson (2019) [78]; Kim and Lee (2018) [86] The cooperation mode of value co-creation can guide the partners to invest in green technology and distribute benefits.…”
Section: Financial Performancementioning
confidence: 99%
See 1 more Smart Citation